INOVASI DIGITAL PENGEMBANGAN DESA WISATA WAE REBO SEBAGAI CERMINAN GOOD GOVERNANCE MELALUI E-GOVERMENT - Teo, Yusta Suryono Afri; Mahyuni, Luh Putu (ITB AAS Indonesia Surakarta, 2023)
This study aims to analyze the development strategy of Wae Rebo village tourism and government innovations in creating digital tourist destinations as a reflection of good governance through e-government. This research used qualitative methods and was conducted in Wae Rebo Traditional Tourism Village in Satar Lenda Village, West Satar Mese District, Manggarai Regency, NTT Province. The sampling used was purposive sampling, there were 12 people from the government, tourism development institutions, traditional village leaders, business actors and tourists. Data collection techniques utilize interviews, observation and documentation. Data analysis was carried out through data collection, data reduction, data presentation, and inference. The study results found that the strategy carried out for the development of rebo village tourism was by forming a village development institution and supporting the private sector and government support to create promotional promotions through a unique website containing detailed and complete information about wae rebo tourism village. It is hoped that the website can increase tourist visits and reflect good governance through e-government. Future research is expected to examine the impact of implementing Wae Rebo village tourism promotion through the website.